A kinome-wide selective radiolabeled TrkB/C inhibitor for in vitro and in vivo neuroimaging: synthesis, preclinical evaluation, and first-in-human - Bernard-Gauthier, Vadim; Mahringer, Anne; Fricker, Gert; Wängler, Björn (Journal of medicinal chemistry, 2017)
The proto-oncogenes NTRK1/2/3 encode the tropomyosin receptor kinases TrkA/B/C which play pivotal roles in neurobiology and cancer. We describe herein the discovery of [11C]-(R)-3 ([11C]-(R)-IPMICF16), a first-in-class positron emission tomography (PET) TrkB/C-targeting radiolabeled kinase inhibitor lead. Relying on extensive human kinome vetting, we show that (R)-3 is the most potent and most selective TrkB/C inhibitor characterized to date. It is demonstrated that [11C]-(R)-3 readily crosses the blood-brain barrier (BBB) in rodents and selectively binds to TrkB/C receptors in vivo, as evidenced by entrectinib blocking studies. Substantial TrkB/C-specific binding in human brain tissue is observed in vitro, with specific reduction in the hippocampus of Alzheimer’s disease (AD) versus healthy brains. We additionally provide preliminary translational data regarding the brain disposition of [11C]-(R)-3 in primates including first-in-human assessment. These results illustrate for the first time the use of a kinome-wide selective radioactive chemical probe for endogenous kinase PET neuroimaging in human.